Políticas educacionais, conflitividade e convivência escolar entre adolescentes: intervenções político-pedagógicas no IFRS-Campus Sertão - Silva, Gabriele Albuquerque (2017)
The research that resulted in the dissertation "Educational policies, conflict and school convivence among adolescents: political-pedagogical interventions in IFRS - Campus Sertão" was developed from a qualitative research focusing on conflicting relations established among the adolescent students of the Federal Institute of Rio Grande do Sul - Campus Sertão. The method applied was the case study, based on participatory observation, documentary analysis and semi-structured interviews. The main objective is to explore the school conflict among adolescents based on the political and pedagogical action of the IFRS - Campus Sertão, aiming to comprehend its manifestations and to discuss about prevention policies and intervention in the management of school conflicts. In the educational context of the Institute, in which the agents intervene daily, the research was limited to the adolescents of two technical integrated to the high school courses: the Agriculture Course and the Course of Maintenance and Support in Informatics. Initially, a contextualisation of the campus was carried out, highlighting its sixty- year trajectory as an educational institution, its structure and its internal regulations, especially the ones about disciplinary issues. Subsequently, school conflicts and their different forms of manifestation were approached from selected bibliographical references to substantiate the study on the basis of a conceptual model composed of violent conflict (harmful to the educational process and human coexistence) and nonviolent conflict (essential for a democratic coexistence in which there is room for dialogue). Afterwards, an analysis of Brazilian educational policies was carried out from the point of view of coexistence and violence in the school context, evidencing the lack of policies that face more deeply the problem of conflict. The study with the campus adolescents highlighted manifestations of violent conflict and power relations among students, as well as political-pedagogical practices developed by educators to intervene in violent situations and develop non -violent relations of coexistence. The research showed that IFRS - Campus Sertão is an institution that faces daily situations of conflict between students (divergences of opinions, issues of coexistence, bullying, the breach of institutional norms). However, there is an effort to transform a violent conflict into relationships based on respect for diversity, through interdisciplinary work and based on dialogue. In this process, the work of the Department of Student Assistance and the role of the nuclei existing on campus are relevant, which act in the perspective of affirmative action. Even though there is a concern on the part of the management of contacts as conflicting relationships, it is necessary to deepen the understanding about school conflicts, to build technically more improved actions and to potentiate the existing human and structural resources. The educators’ institutional experience is very rich in the accomplishment of an interdisciplinary work, and the case study collaborates in the understanding of the school conflict phenomena in the Brazilian society. It is evident the need to qualify the institutional practices and to advance in the development of educational policies that promote inclusive and democratic relations and contribute to signify school spaces as promoters of a citizen's formation. Coexistence in the educational context is a constant challenge. Situations of school violence negatively impact the teaching-learning process, which demands policies that aims the transformation of exclusionary practices into dialogic and democratic educational processes.